The Influence of Arctic Landfast Ice on Seasonal Modulation of the M2 Tide. Issue 5 (3rd May 2021) - Bij de Vaate, I.; Vasulkar, A. N.; Slobbe, D. C.; Verlaan, M.
Abstract: Seasonal modulation of the M2 tide has been quantified for the entire Arctic Ocean and connected regional seas, using tidal harmonic analysis of water levels derived from Synthetic Aperture Radar altimetry. Results are compared to numerical simulations that model the effect of two limiting cases of seasonal landfast ice cover on the M2 tide. The largest seasonal modulation (up to 0.25 m) is observed along coastlines and in bays. Locally, the presence of landfast ice decreases amplitudes, but in some cases, the opposite effect was observed further afield. In most of the Arctic, winter months experience a later arrival of the tide, except for Hudson Bay where phase advance is observed. Most of the altimeter‐derived seasonal modulation could be explained by the modeled impact of landfast ice. However, particularly in the Hudson Bay system there is a discrepancy between model‐ and altimeter‐derived seasonal modulation. This suggests that other seasonal processes are important. Finally, results suggest that the consequences of variations in Arctic landfast ice are not restricted to the Arctic, but affect tidal water levels on a global scale. Plain Language Summary: Tides are an important force in shaping the Arctic climate and environment. It is known that seasonal changes in Arctic sea ice affect local tides. However, observations of these changes are scarce, and many tide models still treat tides as constant throughout the year. As a first of its kind, our study maps the seasonal variations in the main semi‐diurnal tide for the entire Arctic region, based on water levels derived from satellite altimetry. To better understand the relation between observed variations in tides and the seasonal sea ice cycle, two models were run with annual maximum and minimum extents of landfast (immobile) sea ice cover. Observations and simulations both show reduced tidal amplitudes in winter months in most regions where landfast ice is present, but some other regions experience increased tides. Not all of the observed seasonal variation in tides could be explained by the influence of sea ice, indicating that further research is needed, to include other seasonal processes. Our models show that seasonal changes in Arctic sea ice cover can also affect global tides. Key Points: Seasonal modulation of the M2 tide is observed across the Arctic with amplitude changes up to 0.25 m in Hudson Bay and on the Russian shelf Landfast ice can have a dual effect on tides, causing local amplitude decrease but tidal amplification further afield Seasonal variations in Arctic landfast ice affect modeled tides on a global scale